123 Establishing Standard Performance Measures in Adult Traumatic Brain Injury Patients: A Nationwide Inpatient Sample Database Study. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Corliss, Brian M.; Hooten, Kristopher G.; Gul, Sarah Shireen; Neal, Dan; Murad, Gregory J.; Rahman, Maryam
Abstract: INTRODUCTION: The Agency for Healthcare Research and Quality (AHRQ) patient safety indicators (PSIs) and Centers for Medicare and Medicaid Services hospital-acquired conditions (HACs) are publicly reported metrics that illustrate the overall quality of care of an institution. The incidences of PSIs and HACs in traumatic brain injury (TBI) patients were determined using the nationwide inpatient sample (NIS) database. METHODS: The NIS database was queried for patients admitted with International Classification of Diseases, Ninth Revision diagnosis codes consistent with TBI. The incidences of PSIs and HACs were determined for TBI patients and compared between teaching and non-teaching hospitals. A logistic regression model was created to estimate the effects of insurance status on PSIs, HACs, and patient outcomes. RESULTS: There were 15 403 total PSIs among 24 012 TBI patients. Teaching hospitals had a higher incidence of PSIs (653 per 1000 patients) compared to non-teaching hospitals (615 per 1000 patients; P = .0016) as well as a higher fraction of patients suffering at least 1 PSI (54.0% vs 50.8%; P = .004). There were only 165 HACs among 24 012 TBI patients. There was no significant difference between teaching and non-teaching hospitals in incidence of HACs; HACs were more common, however, in Medicaid patients compared to privately insured patients (8.9 vs 5.0 HACs/1000 patients; P = .0015.) Multivariate analyses comparing the Medicaid and private insurance patients demonstrated no difference between the groups in either poor outcome or mortality; however, the length of stay for Medicaid patients was prolonged 2.0 days compared with private insurance (95% CI: [1.35, 2.62]; P < .0001). CONCLUSION: Clinical outcomes following TBI were not affected by insurance status. Patients treated in teaching hospitals suffered a higher incidence of PSIs, although this was not controlled for injury severity. These data may be used as reference values for hospitals reporting their own rates and seeking to improve the quality of care they provide for TBI patients.